Re-interpretation of Islamic Transaction Principles in Economic Activities - Johar Johar; Maghfirah Maghfirah (Jurnal Madania)
Muʻamalah, as a human activity related to devotion to Allah, must abide by the rules established by Islamic law for the benefit of society and the maintenance of rights and duties among people. Therefore, the purpose of this paper is to provide a comprehensive and applicable explanation of the reinterpretation of Islamic transactional principles in 21st century economic activities. This article is a library study using qualitative methods. Methods for collecting document data from relevant journals and books. It is then analyzed using content analysis methods. The result of this research is the principles of Islamic transactions: (1) mashlahah as an indicator of transactions, (2) justice in transactions, and (3) prohibition of all transactions involving ribâ, gharâr, tadlîs, tahkîr, maysîr, and risywah. The similarity between the study and previous studies lies in the concept and principles of Islamic transactions, but the difference is that this study fully explains the principles of Islamic transactions, with examples of their application in economic activities.